2011
DOI: 10.1097/igc.0b013e318228f314
|View full text |Cite
|
Sign up to set email alerts
|

Do Surgical Techniques Used in Groin Lymphadenectomy for Vulval Cancer Affect Morbidity Rates?

Abstract: We recommend the use of subcuticular suture for wound closure. Patients who undergo lymphadenectomy with a node count per groin of more than 7 should be closely monitored for lymphedema and referred promptly to specialist services. The prolonged use of suction drainage may increase the risk of lymphedema.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 9 publications
1
18
1
Order By: Relevance
“…Therefore, as concerns surgical complications following lymphadenectomy, we reported a complication rate of 33%, similar to those reported in the international literature [22][23][24][25][26][27][28][29][30][31][32][33][34][35]15]. Most common complications were wound breakdown and lymphedema.…”
Section: Discussionsupporting
confidence: 86%
“…Therefore, as concerns surgical complications following lymphadenectomy, we reported a complication rate of 33%, similar to those reported in the international literature [22][23][24][25][26][27][28][29][30][31][32][33][34][35]15]. Most common complications were wound breakdown and lymphedema.…”
Section: Discussionsupporting
confidence: 86%
“…A recent prospective Dutch study by Pouwer and colleagues 11 of volume-controlled versus short-duration drainage following IFL in 141 vulvar cancer patients (251 groins) demonstrated that volume-controlled drainage (median duration, 13 days) was associated with significantly fewer complications compared with short drainage (median duration, 5 days). Our findings are not consistent with the studies by Walker et al 9 and Pouwer et al because we did not observe any difference in postoperative outcomes with duration of drain usage. This may reflect the limitations of retrospective studies with a small number of events and limited statistical power or differences between the study populations.…”
Section: Discussioncontrasting
confidence: 99%
“…9 Walker and colleagues 9 conducted a retrospective analysis of 56 vulvar cancer patients who underwent groin dissection, 44 of whom had an inguinal suction drain, and did not report a reduction in surgical morbidity. However, Walker et al 9 did report that a short duration of drain use (1Y3 days) was associated with wound breakdown, and a long duration of use (Q7 days) was associated with higher rates of lymphedema.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Web sites that adhere to this principle will distinguish themselves while providing useful and relevant information to patients and the healthcare professionals that accompany them. Research shows that some healthcare professionals wish to identify patients at risk for developing lymphedema and refer them for preventive measures (Walker et al, 2011); the Internet could be a suitable support for them and their patients. When designing a Web site, an organization should cite the original sources used and regularly update or review the content.…”
Section: Implications For Practicementioning
confidence: 99%